Application of Electrical Impedance Measurements’ Method for Studies of Bubble Flows - I. A. Konovalov; A. A. Chesnokov; A. A. Barinov; S. M. Dmitriev; A. E. Khrobostov; M. A. Makarov (Приборы и методы измерений, 2021)
One of the important tasks in carrying out a computational justification of the reliability and safety of equipment that is part of the projected nuclear power plants today is the modeling of the bubbly regime of the coolant flow. In this regard the aim of this work is the use of extended methods of using matrix conductometric systems which are widespread in research practice for study of gas-liquid flows.The work uses a method of primary processing of experimental data aimed at eliminating of excess conductivity in the cells of the developed wire mesh sensor which makes it possible to obtain the values of the true volumetric gas content in the investigated area.Subsequent analysis of the possibilities to estimate the volumes of registered gas bubbles by the gradient method as well as the size of the interface in the sensor cells which plays a key role in modeling the interfacial heat and mass transfer.Comparison of readings values with the control instruments cues showed a good agreement. The presented work is an adaptation of the use of a conductometric measuring system for the study of multicomponent flows with the aim of further application for the study of two-component flows in the channels of the core simulator using wire mesh sensors.